ANALISIS PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Thio, Karen Trifena; Susilandari, Caecilia Atmini (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2020)
This research aims to analyse the development of firm value of the manufacture companies. Based on the data of the Indonesian Ministry of Industry, it shows that value added for manufacturing companies increase, and also increase the contribution of manufacture companies to the development of economic of Indonesia. Profitability, size, growth, and capital structure as independent variables are used to identify the influence of manufacture firm value. There shall be 166 samples of listed manufacture companies in Indonesia Stock Exchange in 2014-2018 which suit for criteria needed, and the data processing using multiple linear regression. The research result shows that only profitability and size variables which have positive significant influences to firm value variable on t- test. Besides, growth and capital structure variables are vice versa.